Students of secondary schools about Fetal Alcohol Spectrum Disorders (FASD) - Banach, Marek; Matejek, Józefa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In recent years, a new entity called Fetal Alcohol Syndrome which is marked Q.86.0 in the nomenclature of the International Health Organization appeared in Polish literature. The disease is a result of alcohol consumption by pregnant women. It seems that due to the large scale of the disease, preventive actions should be taken, for example by providing the necessary knowledge to secondary school students. This is especially important in the period of adolescence when they enter adulthood, often drinking alcohol and taking the first steps related to their sex life. The scale used in research allows us to specify the understanding and knowledge of youth in this regard. In this article we present the results of studies conducted in the years 2008 and 2016 among youth groups from senior years of High School in Krzeszowice.
Keywords: alkohol; fetal alkohol syndrome; youth; attitude; knowledge about FASD; threats